Toward a new Federal law on arbitration - Carbonneau, Thomas E. (New York : Oxford University Press, 2014)
This title endeavours to repair the long-standing problem of updating the official text of the Federal Arbitration Act (FAA). In this book, Thomas E. Carbonneau proposes to transform the FAA into a genuine national law of arbitration, based exclusively on the federal rules applicable to arbitration. He argues for necessary change in the federal law of arbitration that will not only benefit commercial interests and the US economy, but also provide protection for smaller individual interests, such as consumers and employees.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on November 4, 2014).
Keywords: Arbitration and award -- United States